What drives First-Generation College Students to be resilient in pursuing higher education in Africa? - Jacob Oppong Nkansah; Yusuf Oldac Ikbal (Social Sciences and Humanities Open, 2024)
This study explored First-Generation College Students' (FGCS) resilience in pursuing higher education in Ghana. FGCS is conceptualised as learners whose parents did not complete or attend university and who encountered challenges that could have impaired their resilience to pursue higher education in Ghana. This paper employed a conceptual framework built from the Ecological and Resilience theories to investigate FGCS’ resilience in pursuing higher education and how this resilience manifests to ensure FGCS's success. The study used a phenomenological design and Snowballing to interview 12 selected participants at a large public university in Ghana. The findings demonstrate how the resilience of FGCS in higher education is influenced by personal, societal, family, and institutional factors, which have resulted in the formation of self-agency and a range of resilient character traits. This paper recommends that a collaborative effort between universities, the Ministry of Education, and policymakers in Ghana and abroad is needed to influence FGCS policies and practices that reach to such vulnerable groups in the higher education environment.